Isotropic three-dimensional communicated porous wave-absorbing ceramic and preparation method thereof
The isotropic three-dimensional connected porous wave absorbing ceramic prepared by vacuum freeze-drying and high-temperature thermal cracking solves the problems of cumbersome and high cost in the preparation process of existing ceramic materials, achieves low-cost and efficient wave absorbing performance, and has good high-temperature resistance and processability.
Patent Information
- Application Number
- CN202411882651.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-03-14
AI Technical Summary
The existing preparation method of three-dimensional connected porous structure wave absorbing ceramic materials has problems of cumbersome process and high cost, and the use of a large amount of organic matter is not environmentally friendly.
The isotropic three-dimensional connected porous wave absorbing ceramic ceramics are prepared by dispersing ceramic powder and lignocellulose in deionized water to form a mixed solution, then freeze and vacuum freeze dry, and finally thermal cracking is performed.
It realizes isotropic three-dimensional connected porous ceramics with low production cost, simple process and excellent wave absorption performance. It has good high temperature resistance, processability and electromagnetic wave absorption performance, and has a wide range of application prospects.
Smart Images

Figure CN119613141A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of porous ceramic wave-absorbing materials, and in particular to an isotropic three-dimensional interconnected porous wave-absorbing ceramic and a preparation method thereof. Background Art
[0002] With the continuous advancement of electronic information technology, electromagnetic waves, as a main way of information transmission, play an important role in wireless communications and national defense science and technology. However, while new technologies bring convenience, they also have disadvantages. Excessive electromagnetic pollution not only brings health risks to people's lives, but also interferes with the normal operation of instruments and electronic equipment, causing communication equipment failure and aircraft out of control, leading to serious consequences. Therefore, the development of efficient absorbing materials has become the focus of social attention.
[0003] As a potential absorbing material, ceramics have excellent corrosion resistance and oxidation resistance and can be used in harsh environments. And because of its good thermal stability and light weight, it has attracted much attention from researchers at home and abroad, especially in the field of high-temperature absorbing, such as Al2O3, SiO2 and SiC. However, ceramic absorbing materials also have shortcomings. The low conductivity and strong binding ability of original ceramic materials to electrons are the main reasons for their unsatisfactory dielectric properties, which also hinders their application in high-performance absorbing materials. In order to solve this problem, component design and microstructure improvement have been proven to be the most convenient and effective methods to improve its absorbing performance. It mainly uses composite metal oxides, carbon-based materials and other materials to change the dielectric constant and thus improve the absorbing performance, or introduces more interface polarization and increases loss through structural design (core-shell, hollow or porous structure, etc.), thereby improving impedance matching characteristics.
[0004] Three-dimensional interconnected porous structure absorbing materials have a large number of open pores and a large specific surface area, which is conducive to achieving better impedance matching while building lightweight materials; in addition, the porous structure will cause multiple reflections and scattering of microwaves, thereby making the electromagnetic waves propagate a longer path and consuming more electromagnetic energy; and the porous structure makes the absorbing material lighter. However, the current preparation method of three-dimensional interconnected porous structure absorbing ceramic materials has problems such as cumbersome preparation process and high cost, and a large amount of organic matter is used in the preparation process, which is not green and environmentally friendly. Summary of the invention
[0005] In order to solve the above technical problems, the purpose of the present invention is to provide an isotropic three-dimensional interconnected porous absorbing ceramic and a preparation method thereof, so as to solve the problems of complicated preparation process and high cost of existing absorbing ceramic materials.
[0006] The technical solution of the present invention to solve the above technical problem is as follows: a method for preparing an isotropic three-dimensional interconnected porous absorbing ceramic is provided, comprising the following steps:
[0007] (1) dispersing ceramic powder and wood cellulose in deionized water and stirring to obtain a mixed solution;
[0008] (2) pouring the mixed solution obtained in step (1) into a mold, freezing it, and then freeze-drying it under vacuum, removing the mold, and obtaining a green body;
[0009] (3) thermally cracking the green body obtained in step (2) to obtain an isotropic three-dimensional interconnected porous microwave absorbing ceramic.
[0010] The beneficial effects of the present invention are as follows: the present invention adopts vacuum freeze drying and high temperature thermal cracking to obtain isotropic three-dimensional interconnected porous ceramics with electromagnetic wave absorption performance, and the method can solve the problems of high preparation cost, complex process, and difficult control of wave absorption performance of existing porous wave absorbing materials. The porous wave absorbing ceramics of the present invention have good high temperature resistance, processability and excellent wave absorbing performance, and have potential application prospects in the field of wave absorption.
[0011] On the basis of the above technical solution, the present invention can also be improved as follows:
[0012] Furthermore, in step (1), the mass ratio of ceramic powder, wood cellulose and deionized water is 1:0.06-0.55:5.
[0013] Furthermore, in step (1), the ceramic powder is at least one of SiC whiskers, Si3N4 whiskers, Si powder and C powder.
[0014] Furthermore, in step (1), the microstructure of the wood cellulose is in the form of curled lamellae.
[0015] Furthermore, in step (1), the wood cellulose manufacturer is Funa New Materials Technology (Shanghai) Co., Ltd.
[0016] Furthermore, in step (1), stirring is performed for 3-5 hours.
[0017] Furthermore, in step (2), the mixture is frozen at -25 to -30°C for 5 to 8 hours.
[0018] Furthermore, in step (2), the mixture is frozen at -20°C for 5-8 hours.
[0019] Furthermore, in step (2), vacuum freeze drying is performed for 24-36 hours.
[0020] Furthermore, in step (2), the mold material is polyethylene.
[0021] Furthermore, in step (3), thermal cracking is carried out under the protection of an inert atmosphere or under vacuum conditions.
[0022] Furthermore, the inert atmosphere is Ar or N2.
[0023] Furthermore, in step (3), thermal cracking is performed at 1300-1500° C. for 2-4 hours.
[0024] The invention also provides isotropic three-dimensional interconnected porous wave-absorbing ceramics prepared by the method.
[0025] The present invention also provides application of the isotropic three-dimensional interconnected porous wave-absorbing ceramic in the preparation of wave-absorbing materials.
[0026] The present invention has the following beneficial effects:
[0027] 1. This document uses wood cellulose to construct a template for a three-dimensional interconnected pore structure. During the vacuum freeze-drying process, ice crystals are removed by sublimation, which will not cause the collapse of the overall structure, and the three-dimensional interconnected porous structure is retained.
[0028] 2. During the vacuum freeze-drying process of the present invention, wood cellulose spontaneously aggregates and forms a cellulose template. At the same time, the ceramic powder is evenly wrapped in the cellulose template. During the sintering and heating process, the wood cellulose template is gradually ablated, and the ceramic powder is interconnected through high-temperature solid-phase mass transfer to form an isotropic three-dimensional interconnected porous ceramic structure with uniform structure and controllable size.
[0029] 3. The three-dimensional interconnected porous structure of the present invention provides a large specific surface area, so that electromagnetic waves are scattered and reflected multiple times inside the material, thereby enhancing its wave absorption capacity. At the same time, by adjusting the content of lignocellulose, the pore size of the lignocellulose template can be regulated, and then the pore size of the three-dimensional interconnected structure ceramic can be adjusted to further regulate the electromagnetic wave absorption performance. In addition, the three-dimensional interconnected porous structure can form a good acoustic impedance match with the air, which helps to reduce reflection losses and improve absorption efficiency.
[0030] 4. The dried green body with three-dimensional interconnected pore structure of the present invention produces a carbon-rich, highly aromatic and highly stable solid product through high-temperature pyrolysis under inert atmosphere conditions. The biomass carbon formed by high-temperature pyrolysis of wood cellulose will produce polarization in the electromagnetic field, causing electromagnetic waves to be repeatedly reflected and lost inside the material. The conductivity and dielectric loss of the material will cause part of the electromagnetic wave energy to be converted into heat energy, improving the room temperature wave absorption performance of the material.
[0031] 5. The three-dimensional interconnected porous absorbing ceramic of the present invention has uniform pore structure, controllable size, certain mechanical strength, processability, low density, high porosity, large specific surface area, good thermal stability and chemical stability, etc., and can be used as a high-temperature resistant absorbing material with application potential;
[0032] 6. The three-dimensional interconnected porous absorbing ceramic preparation process of the present invention is simple, short in cycle, low in cost, uses few raw material components, is cheap and easy to obtain, and has good stability and repeatability. In addition, its simple and green preparation process can be extended to the recycling of natural plant waste, making it have a wide range of application prospects in the electromagnetic field. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 The figure is a flow chart of the preparation of the isotropic three-dimensional interconnected porous absorbing ceramic of the present invention;
[0034] Figure 2 This is a scanning electron microscope image of lignocellulose;
[0035] Figure 3 is the scanning electron microscopy image of the lignocellulose template after vacuum freeze drying;
[0036] Figure 4 This is the appearance diagram of the reflectivity test of the sample in Example 1;
[0037] Figure 5 This is a test curve diagram of the reflectivity of the sample in Example 1; DETAILED DESCRIPTION
[0038] The principles and features of the present invention are described below in conjunction with the accompanying drawings. The examples are only used to explain the present invention and are not used to limit the scope of the present invention. If specific conditions are not specified in the embodiments, they are carried out according to normal conditions or conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0039] In the following examples, the manufacturer of wood cellulose is Funa New Materials Technology (Shanghai) Co., Ltd., and the electron microscope images are shown in Figure 2 .
[0040] Embodiment 1:
[0041] An isotropic three-dimensional interconnected porous absorbing ceramic, the preparation method of which comprises the following steps (the preparation flow chart is shown in Figure 1 ):
[0042] (1) Dispersing ceramic powder (SiC whisker) and wood cellulose in deionized water, stirring for 4 hours, and mixing evenly to obtain a mixed solution; wherein the mass ratio of ceramic powder, wood cellulose and deionized water is 1:0.2:5;
[0043] (2) pouring the mixed solution obtained in step (1) into a polyethylene mold, and after the mixed solution is leveled and evenly covers the surface of the polyethylene mold, immediately placing it in a laboratory refrigerator, and then freezing it at -20°C for 6 hours. After the mixed solution is completely transformed into an ice-like solid, the polyethylene mold and the sample are transferred to a vacuum freeze dryer, and vacuum freeze-dried for 30 hours. The polyethylene mold is removed to obtain a green body (a three-dimensional interconnected porous structure);
[0044] (3) In a tubular furnace under the protection of an inert atmosphere of Ar, the green body obtained in step (2) is thermally cracked at 1400° C. for 3 h to obtain an isotropic three-dimensional interconnected porous microwave absorbing ceramic.
[0045] Embodiment 2:
[0046] An isotropic three-dimensional interconnected porous absorbing ceramic, the preparation method of which comprises the following steps (the preparation flow chart is shown in Figure 1 ):
[0047] (1) Dispersing ceramic powder (Si3N4 whiskers) and wood cellulose in deionized water, stirring for 3 hours, and mixing evenly to obtain a mixed solution; wherein the mass ratio of ceramic powder, wood cellulose and deionized water is 1:0.06:5;
[0048] (2) pouring the mixed solution obtained in step (1) into a polyethylene mold, and after the mixed solution is leveled and evenly covers the surface of the polyethylene mold, immediately placing it in a laboratory refrigerator, and then freezing it at -25°C for 5 hours. After the mixed solution is completely transformed into an ice-like solid, the polyethylene mold and the sample are transferred to a vacuum freeze dryer, and vacuum freeze-dried for 24 hours. The polyethylene mold is removed to obtain a green body (a three-dimensional interconnected porous structure);
[0049] (3) In a tubular furnace under the protection of an inert atmosphere of N2, the green body obtained in step (2) is thermally cracked at 1300°C for 4 hours to obtain an isotropic three-dimensional interconnected porous absorbing ceramic.
[0050] Embodiment 3:
[0051] An isotropic three-dimensional interconnected porous absorbing ceramic, the preparation method of which comprises the following steps (the preparation flow chart is shown in Figure 1 ):
[0052] (1) Dispersing ceramic powder (Si powder and C powder) and wood cellulose in deionized water, stirring for 5 hours, and mixing evenly to obtain a mixed solution; wherein the mass ratio of ceramic powder, wood cellulose and deionized water is 1:0.55:5;
[0053] (2) pouring the mixed solution obtained in step (1) into a polyethylene mold, and after the mixed solution is leveled and evenly covers the surface of the polyethylene mold, immediately placing it in a laboratory refrigerator, and then freezing it at -30°C for 5 hours. After the mixed solution is completely transformed into an ice-like solid, the polyethylene mold and the sample are transferred to a vacuum freeze dryer, and then vacuum freeze-dried for 36 hours, and the polyethylene mold is removed to obtain a green body (a three-dimensional interconnected porous structure);
[0054] (3) Under vacuum conditions in a tubular furnace, the green body obtained in step (2) is thermally cracked at 1500° C. for 2 h to obtain an isotropic three-dimensional interconnected porous microwave-absorbing ceramic.
[0055] Comparative Example 1:
[0056] Step (1) does not include ceramic powder, and the rest is the same as in Example 1.
[0057] Test example
[0058] 1. The green bodies obtained in Example 1 and Comparative Example 1 were subjected to SEM examination. The results are shown in Figure 3 ( Figure 3 (a)-(c) are comparative example 1, and (d)-(f) are example 1).
[0059] Depend on Figure 3 It can be seen that (a)-(c) illustrate that cellulose can obtain a three-dimensional interconnected pore structure after freeze-drying; (d)-(f) can be seen that after the ceramic powder is coated on the cellulose template, after magnification, it can be seen that the microstructure of the silicon carbide whisker is in the shape of short rods.
[0060] 3. The isotropic three-dimensional interconnected porous absorbing ceramics prepared in Example 1 were tested for reflectivity using the bow frame method. The results are shown in Figure 4-5 ( Figure 5 Measured at 2-18 GHz).
[0061] Depend on Figure 4-5 It can be seen that the isotropic three-dimensional interconnected porous microwave-absorbing ceramics prepared in the present invention still have excellent microwave-absorbing performance at high temperatures.
[0062] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing an isotropic three-dimensional interconnected porous microwave-absorbing ceramic, characterized in that: The following steps are involved: (1) dispersing ceramic powder and wood cellulose in deionized water and stirring to obtain a mixed solution; (2) pouring the mixed solution obtained in step (1) into a mold, freezing it, and then freeze-drying it under vacuum, and removing the mold to obtain a green body; (3) thermally cracking the green body obtained in step (2) to obtain an isotropic three-dimensional interconnected porous microwave absorbing ceramic.
2. The method for preparing the isotropic three-dimensional interconnected porous absorbing ceramic according to claim 1, characterized in that: In step (1), the mass ratio of ceramic powder, wood cellulose and deionized water is 1:0.06-0.55:
5.
3. The method for preparing the isotropic three-dimensional interconnected porous absorbing ceramic according to claim 1, characterized in that: In step (1), the ceramic powder is at least one of SiC whiskers, Si3N4 whiskers, Si powder and C powder.
4. The method for preparing the isotropic three-dimensional interconnected porous absorbing ceramic according to claim 1, characterized in that: In step (1), the microstructure of the wood cellulose is in the form of curled lamellae.
5. The method for preparing the isotropic three-dimensional interconnected porous absorbing ceramic according to claim 1, characterized in that: In step (2), the mixture is frozen at -25 to -30°C for 5 to 8 hours.
6. The method for preparing the isotropic three-dimensional interconnected porous absorbing ceramic according to claim 1, characterized in that: In step (2), vacuum freeze drying is performed for 24-36 hours.
7. The method for preparing the isotropic three-dimensional interconnected porous absorbing ceramic according to claim 1, characterized in that: In step (3), thermal cracking is carried out under the protection of an inert atmosphere or under vacuum conditions.
8. The method for preparing the isotropic three-dimensional interconnected porous absorbing ceramic according to claim 1, characterized in that: In step (3), thermal cracking is carried out at 1300-1500°C for 2-4h.
9. An isotropic three-dimensional interconnected porous absorbing ceramic obtained by the preparation method of the isotropic three-dimensional interconnected porous absorbing ceramic according to any one of claims 1 to 8.
10. Use of the isotropic three-dimensional interconnected porous absorbing ceramic according to claim 9 in the preparation of absorbing materials.